Motivations to Choose Dentistry among Dental Students of Tabriz University of Medical Sciences in 2013 - Milad Ghanizadeh; Mahdi Rahbar Sabalankandi; Ali Hafezeqoran; Mahdi Sadeghi (Tabriz University of Medical Sciences, 2013)
Introduction: One of the most important decisions in an individual's life is to choose the field of study. Then, lots of money and time are spent in order to gain required skills and competencies of the job. According to previous studies, job changing is rarely possible for dentists which is due to the importance of field choice. The present study aimed at determining motivations to choose dentistry field among dental students of Tabriz University of Medical Sciences in 2013. Methods: In this cross-sectional descriptive study, 245 questionnaires were distributed among all dental students of Tabriz University of Medical Sciences and finally 200 questionnaires (81%) were returned. The questionnaire was made by the researcher and its reliability and validity were proved. Data was analyzed using descriptive and analytical statistical methods and SPSS. Results: The students referred to appropriate occupational opportunity and social position as the most important reasons to choose the field while possible abroad job opportunities had the least effect in this regard. Income among males, family advice and serving society among females were the most important factors. Conclusion: Students reported social respect, occupational independency and serving society as the most important motivational factors to choose the field. Providing correct information, the opportunity can be used to promote dentists position in society and improve public attitude toward this field.